Asuhan Keperawatan Keluarga Melalui Penerapan Kombinasi Akupresur (Titik LV3) dengan Relaksasi Nafas Dalam Terhadap Masalah Keperawatan Ketidakefektifan Manajemen Regimen Terapeutik - Suci Indah Putri; Candra Saputra; Ifon Driposwana; Donny Hendra (Journal of Innovative and Creativity, 2025)
Families have an important role in improving health status such as recognizing health problems, providing care for sick family members, making appropriate action decisions, and referring to health facilities, especially in overcoming hypertension. Hypertension is persistent or continuous blood pressure with systolic blood pressure > 140 mmHg and diastolic blood pressure > 90 mmHg. Nursing problems that often arise in families with hypertension are Ineffectiveness of Therapeutic Regimen Management and Knowledge Deficit. One of the non-pharmacological treatments for hypertension is the combination of Acupressure Therapy (LV3 Point) with Deep Breath Relaxation. This therapy provides benefits in lowering blood pressure and giving a sense of relaxation to hypertensive patients. The purpose of this KIAN is to provide an overview of the results of the nursing profession practice “Family Nursing Care Through the Application of Acupressure Combination (Point Lv3) With Deep Breath Relaxation Against Nursing Problems of Ineffectiveness of Therapeutic Regimen Management” in Rw 02 Kelurahan Tuah Negeri Pekanbaru. The method used is a case study with data collection techniques through interviews, observation and direct physical examination. The sample of this study was a patient with hypertension totaling 1 family. The research was conducted for 5 days, namely from November 25-29, 2024. The implementation of the combination of acupressure therapy (LV3 point) with deep breath relaxation was carried out for 3 days. The results of development using the results criteria show that there is a significant influence between before being given a combination of acupressure (LV3 point) with deep breath relaxation.